Marine Applications of the Fast Marching Method - Garrido, Santiago; Alvarez, David; Moreno, Luis E. (Frontiers in Robotics and AI, 2020)
Path planning for marine applications is a special case of the more general problem for mobile robots since, in addition to avoid colliding with obstacles, it is necessary to optimize the cost function taking into account water currents. In this paper, several solutions for ship motion planning based on the Fast Marching Method are proposed. The basic method focus on collision avoidance and optimal planning and, later on, using the same underlying method, the influence of marine currents in the optimal path planning is detailed. Finally, the application of these methods to consider marine robot formations is presented.